ChatGPT-Supported Higher Education in Tanzania: A ‎Systematic Review of Evidence Informing a Proposed ‎Instructional Clarity–Social Presence Model - James George Hatibu; Anang Sujoko (Yayasan Darussalam Bengkulu, 2026)
This systematic literature review aimed to synthesize evidence on instructional clarity and attributed social presence in ChatGPT-supported higher education and to develop a conceptual serial-mediation model for future empirical testing in Tanzanian higher education. Following the PRISMA 2020 reporting guideline, records were retrieved from Scopus and ScienceDirect, yielding 301 records; after removing three duplicates and excluding 239 records during title or abstract and full-text screening, 59 studies were included in the narrative synthesis and appraised using the Mixed Methods Appraisal Tool (MMAT). The findings showed consistent evidence across multiple contexts that instructional clarity and social presence were independently associated with engagement, perceived usefulness, and participation. However, only a small number of studies examined social presence as a mediator of the effects of instructional clarity on learning-related outcomes, and none were conducted in Tanzania or jointly examined both constructs. A supplementary search of a broader 1,000-record corpus likewise identified no studies jointly indexing instructional clarity and social presence or combining either construct with a Tanzanian context. These findings indicate a contextual and pathway-specific evidence gap and support the development, rather than empirical validation, of a proposed serial pathway linking instructional clarity, social presence, engagement, perceived usefulness, and active participation. The review is limited by its reliance on two databases and ChatGPT-specific evidence. Future research should empirically test the proposed model in Tanzania and other Sub-Saharan African higher-education contexts.